indonesia Presentasi Diri Penyiar Perempuan Di Media Radio Garut - Ahmad, Silmi Halimatusya’diah; Kurniawan, Achmad Wildan; Hermawandi, Yandi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
A radio announcer plays an important role in delivering information and entertainment to listeners. Where female broadcasters have the ability to manage impressions during the program. The purpose of the research is to find out the radio announcer in self-presentation by building an image on the front stage and back stage as a female announcer. The method used is Qualitative Method with Dramaturgy Theory approach by Goffman. The results showed that the front stage setting, female broadcasters have done in accordance with regional settings such as appearance, behavior style, intonation, speaking speed and body language. Backstage usually broadcasters make preparations before broadcasting by looking for material, managing emotions and entering into their lives as housewives, teachers and marketing staff, besides that. While seen from the image, making efforts to interact with professional listeners in accordance with radio station regulations. The impact of this message management not only helps broadcasters in building a strong relationship with the audience but also contributes to the progress and professionalism of the radio, which will give the trust of the audience and will attract advertisements and sponsors for the radio.